WEB-BASED INFORMATION SYSTEM AT SMK NEGERI 1 SUOH - Idris, Muhammad; Suranto, Suranto; Mukodimah, Siti (JELTec (Journal of Learning Technology), 2023)
The Web-Based Academic Information System at SMK Negeri 1 Suoh is a system that makes it easier for students and teachers to carry out Teaching and Learning Activities (KBM), in addition to being web-based, data information can be accessed at an unspecified time and place. In this system, the menu can only be accessed by certain users, namely students/teachers, and administrators. Based on the results of this research, a Web-Based Information System has been developed with a case study at SMKN 1 Suoh. Where in building this system used system development tools, namely Data Flow Diagrams (DFD), Context Diagrams, Entity Relationship Diagrams (ERD) and Flowcharts and using the programming language PHP and HTML and MySQL as the database.